Literature as cultural ecology sustainable texts - Zapf, Hubert 1948- (Bloomsbury Academic, 2017)
"Outlines a new approach to the reading of literary texts. Hubert Zapf considers the ways in which literature operates as a form of cultural ecology, using language, imagination, and critique to challenge and transform cultural narratives of humanity's relationsip to nature. In this way, the book demonstrates the important role that literature plays in creating a more sustainable way of life."